Boatbuilding : a complete handbook of wooden boat construction - Chapelle, Howard I. (Howard Irving) (W.W. Norton, 1994)
Boatbuilding is a practical handbook and boatshop assistant, designed and written to meet the needs of the builder, covering the complete process of wooden boat construction. The text covers all types of craft from flat-bottom rowboats to ocean cruisers and commercial vessels, and aids the builder in overcoming difficulties and discouraging delays resulting from the lack of easily available information on the practical side of boatbuilding.